Natal dispersal in the Southern Ground Hornbill Bucorvus leadbeateri. (4th May 2019) - Carstens, Kate F; Kassanjee, Reshma; Little, Robin M; Ryan, Peter G; Hockey, Philip AR
Abstract : Dispersal is of ecological and evolutionary importance for population biology because it affects a species' ability to expand its range, to colonise new favourable habitats and to increase the likelihood of population persistence. Male birds are mostly philopatric, delaying dispersal or dispersing closer to their natal territories than females. Females tend to disperse further than their male siblings to reduce the chance of inbreeding. Dispersal in the cooperative breeding Southern Ground Hornbill Bucorvus leadbeateri is poorly understood. It is not known how far individuals disperse, or what the difference in dispersal age and distance is between males and females. We investigated dispersal events using field observations of ringed individuals within groups in a study population and resightings in surrounding areas. A total of 113 individuals from 19 groups were ringed during 2005–2015. Of these, 14 were breeding adults who never dispersed. Of the remaining 99, 27 were still present in their natal groups at the end of the study, four deaths were confirmed, 50 disappeared from their group and were never seen again (excluded from further analysis), and 18 were confirmed to have dispersed by direct observations in secondary groups. Median dispersal distance was similar for females and males (22 km and 25 km, respectively). Females dispersed younger than males (eight months post-fledging and 44 months post-fledging, respectively). One male delayed dispersal beyond nine years and all females dispersed before three years post-fledging. These data provide insights into the dispersal dynamics and dispersal propensity of this endangered species. Ways to improve data collection and the study of dispersal in this species are discussed.